If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 3.4n + -2(n + -4) Reorder the terms: 15 = 3.4n + -2(-4 + n) 15 = 3.4n + (-4 * -2 + n * -2) 15 = 3.4n + (8 + -2n) Reorder the terms: 15 = 8 + 3.4n + -2n Combine like terms: 3.4n + -2n = 1.4n 15 = 8 + 1.4n Solving 15 = 8 + 1.4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1.4n' to each side of the equation. 15 + -1.4n = 8 + 1.4n + -1.4n Combine like terms: 1.4n + -1.4n = 0.0 15 + -1.4n = 8 + 0.0 15 + -1.4n = 8 Add '-15' to each side of the equation. 15 + -15 + -1.4n = 8 + -15 Combine like terms: 15 + -15 = 0 0 + -1.4n = 8 + -15 -1.4n = 8 + -15 Combine like terms: 8 + -15 = -7 -1.4n = -7 Divide each side by '-1.4'. n = 5 Simplifying n = 5
| (3x)+(4x-24)=180 | | x^2+1045x+14278=0 | | P=100-0.5q | | 3c-6+2c=10c-2c+6 | | 5u+6v-3(3u-2v)= | | 2n-4m=8 | | 12s^2-13st-4t^2= | | 15x-10=-9x+12 | | 10x+1=2x+5 | | 41-8x=-6x-23, | | 3(3x+4)-2-5-7x=20 | | -7q+8-6+5q=8 | | 3x+16=12x-74 | | -r+7r-3+5r=93 | | w=mt+b | | =2(3s-8)+7 | | -(4x-4)-(-2x-6)+3=-3(x-1)-(6x+2)+3 | | 2b-10b-15+5=8b-40-4b-6 | | 10x^4-21x^2+9= | | 6a+3a=18 | | 3x+14+2x+1=180 | | 11a-4a-18=2a+a+10 | | 9x-5x-x=9 | | 9x-5x-x=19 | | 4x^4+8x^3+3x^2= | | 7c-4c+5-8+c=29 | | 7=x^2+x+8 | | x(x^2-2)=0 | | 0=-8(2t^2-t-45) | | 8m-4m-6-3+5m=63 | | x(x^2-2)-4=0 | | 8q-q+7-4-3q=47 |